Gamified Learning as a Tool for Enhancing Financial Literacy among Diverse Age Groups - Bhavana Pillai; Harshal Pinge; Ankita Pol; Yashada Tembe; Prof. Rahul Naware (International Journal of Scientific Research in Science, Engineering and Technology, 2025)
In today’s world, being financially aware is no longer a luxury—it’s a necessity. Yet, many people, especially younger individuals, still struggle to grasp basic financial concepts. This research presents a financial literacy platform designed to make learning about money simple, accessible, and engaging. The platform offers age-specific learning modules, with curated content for users under 18 and over 18. It also features a chatbot powered by natural language processing (NLP) to help users quickly understand financial terms. Built using Next.js, the platform delivers a smooth user experience while incorporating a gamified approach to make learning about finances more enjoyable. Our goal is to not just educate users but also empower them to make confident and informed financial decisions in their daily lives.